Mechanisms of change in CBT:Does homework matter? - Rees, Clare; McEvoy, P.; Juniper, U.; Nathan, P.; Smith, L. (The Australian Psychological Society Ltd, 2003)
This study investigated the impact of homework compliance and accuracy on clinical outcome for 72 patient's completing group CBT for anxiety and depression. Homework tasks were differentially associated wth symptom relief for anxious and depressed patients, with benefits being more delayed for depressed patients. The findings are discussed in terms of the importance of therapists examining quality as well as quantity of homework tasks.